Nanocell COVID-19 vaccine triggers a novel immune response pathway producing high-affinity antibodies which neutralize all variants of concern - Gao, Steven Y.; Amaro-Mugridge, Nancy B.; Madrid-Weiss, Jocelyn; Petkovic, Nikolina; Vanegas, Natasha; Visvanathan, Kumar; Williams, Bryan R. G.; MacDiarmid, Jennifer A.; Brahmbhatt, Himanshu (Frontiers in Immunology, 2023)
Most current anti-viral vaccines elicit a humoral and cellular immune response via the pathway of phagocytic cell mediated viral antigen presentation to B and T cell surface receptors. However, this pathway results in reduced ability to neutralize S-protein RBDs from several Variants of Concern (VOC) and the rapid waning of memory B cell response requiring vaccine reformulation to cover dominant VOC S-proteins and multiple boosters. Here we show for the first time in mice and humans, that a bacterially derived, non-living, nanocell (EDV; EnGeneIC Dream Vector) packaged with plasmid expressed SARS-COV-2 S-protein and α-galactosyl ceramide adjuvant (EDV-COVID-αGC), stimulates an alternate pathway due to dendritic cells (DC) displaying both S-polypeptides and αGC thereby recruiting and activating iNKT cells with release of IFNγ. This triggers DC activation/maturation, activation of follicular helper T cells (TFH), cognate help to B cells with secretion of a cytokine milieu promoting B cell maturation, somatic hypermutation in germinal centers to result in high affinity antibodies. Surrogate virus neutralization tests show 90-100% neutralization of ancestral and early VOC in mice and human trial volunteers. EDV-COVID-αGC as a third dose booster neutralized Omicron BA. 4/5. Serum and PBMC analyses reveal long lasting S-specific memory B and T cells. In contrast, control EDVs lacking αGC, did not engage the iNKT/DC pathway resulting in antibody responses unable to neutralize all VOCs and had a reduced B cell memory. The vaccine is lyophilized, stored and transported at room temperature with a shelf-life of over a year.